(6x+5y) ( 4x-9y )

Multiplying binomial by binomial worksheets, solved worksheet problems or exercises with step-by-step work, formative assessment as online test, calculator and more learning resources to learn, practice, assess and master the basic math skills of algebra.

Multiplying Binomial by Binomial

Name
Grade
School

Date
Questions20
Score

1

Find the product

(6x+5y) ( 4x-9y )

(6x+5y) ( 4x-9y )

2

Find the product

(a+7b) ( a-5b )

(a+7b) ( a-5b )

3

Find the product

(4y+4x) ( 4y+3z )

(4y+4x) ( 4y+3z )

4

Find the product

(5x+2y) ( 9x+2y )

(5x+2y) ( 9x+2y )

5

Find the product

(5y+4z) ( 4z+6x )

(5y+4z) ( 4z+6x )

6

Find the product

(6x+2y) ( x+6y )

(6x+2y) ( x+6y )

7

Find the product

(10y+2z) ( 2y+3x )

(10y+2z) ( 2y+3x )

8

Find the product

(4y-x) ( 6x-y )

(4y-x) ( 6x-y )

9

Find the product

(9a+b) ( 6a-6b )

(9a+b) ( 6a-6b )

10

Find the product

(2x-2y) ( 5x-3y )

(2x-2y) ( 5x-3y )

11

Find the product

(2x+3y) ( 5y-2z )

(2x+3y) ( 5y-2z )

12

Find the product

(12y+4z) ( 2y+3z )

(12y+4z) ( 2y+3z )

13

Find the product

(2x+4y) ( 9y-2z )

(2x+4y) ( 9y-2z )

14

Find the product

(9a+2b) ( 6a+6b )

(9a+2b) ( 6a+6b )

15

Find the product

(3a+4b) ( 2a+4b )

(3a+4b) ( 2a+4b )

16

Find the product

(3x+3y) ( 4x+5y )

(3x+3y) ( 4x+5y )

17

Find the product

(3x+5y) ( x-y )

(3x+5y) ( x-y )

18

Find the product

(x-4y) ( 2x+3y )

(x-4y) ( 2x+3y )

19

Find the product

(7x-y) ( 9x-2y )

(7x-y) ( 9x-2y )

20

Find the product

(15m-3n) ( 14m-16n )

(15m-3n) ( 14m-16n )

Solved Worksheet Problems

Show All Workout

1

Find the product

(6x+5y) ( 4x-9y )

= 24x^{2}-34xy-45y^{2}

(6x+5y) ( 4x-9y )

= 24x

Solution

= (6x+5y) x (4x-9y)

= (6x) x (4x) - (6x) x (9y) + (5y) x (4x) - (5y) x (9y)

= 24x^{2}-54xy+20yx-45y^{2}

= 24x^{2}-34xy-45y^{2}

= (6x) x (4x) - (6x) x (9y) + (5y) x (4x) - (5y) x (9y)

= 24x

= 24x

2

Find the product

(a+7b) ( a-5b )

= 1a^{2}+2ab-35b^{2}

(a+7b) ( a-5b )

= 1a

Solution

= (a+7b) x (a-5b)

= (a) x (a) - (a) x (5b) + (7b) x (a) - (7b) x (5b)

= 1a^{2}-5ab+7ba-35b^{2}

= 1a^{2}+2ab-35b^{2}

= (a) x (a) - (a) x (5b) + (7b) x (a) - (7b) x (5b)

= 1a

= 1a

3

Find the product

(4y+4x) ( 4y+3z )

= 16y^{2}+12yz+16xy+12xz

(4y+4x) ( 4y+3z )

= 16y

Solution

= (4y+4x) x (4y+3z)

= (4y) x (4y) + (4y) x (3z) + (4x) x (4y) + (4x) x (3z)

= 16y^{2}+12yz+16xy+12xz

= (4y) x (4y) + (4y) x (3z) + (4x) x (4y) + (4x) x (3z)

= 16y

4

Find the product

(5x+2y) ( 9x+2y )

= 45x^{2}+28xy+4y^{2}

(5x+2y) ( 9x+2y )

= 45x

Solution

= (5x+2y) x (9x+2y)

= (5x) x (9x) + (5x) x (2y) + (2y) x (9x) + (2y) x (2y)

= 45x^{2}+10xy+18yx+4y^{2}

= 45x^{2}+28xy+4y^{2}

= (5x) x (9x) + (5x) x (2y) + (2y) x (9x) + (2y) x (2y)

= 45x

= 45x

5

Find the product

(5y+4z) ( 4z+6x )

= 20yz+30yx+16z^{2}+24zx

(5y+4z) ( 4z+6x )

= 20yz+30yx+16z

Solution

= (5y+4z) x (4z+6x)

= (5y) x (4z) + (5y) x (6x) + (4z) x (4z) + (4z) x (6x)

= 20yz+30yx+16z^{2}+24zx

= (5y) x (4z) + (5y) x (6x) + (4z) x (4z) + (4z) x (6x)

= 20yz+30yx+16z

6

Find the product

(6x+2y) ( x+6y )

= 6x^{2}+38xy+12y^{2}

(6x+2y) ( x+6y )

= 6x

Solution

= (6x+2y) x (x+6y)

= (6x) x (x) + (6x) x (6y) + (2y) x (x) + (2y) x (6y)

= 6x^{2}+36xy+2yx+12y^{2}

= 6x^{2}+38xy+12y^{2}

= (6x) x (x) + (6x) x (6y) + (2y) x (x) + (2y) x (6y)

= 6x

= 6x

7

Find the product

(10y+2z) ( 2y+3x )

= 20y^{2}+30yx+4zy+6zx

(10y+2z) ( 2y+3x )

= 20y

Solution

= (10y+2z) x (2y+3x)

= (10y) x (2y) + (10y) x (3x) + (2z) x (2y) + (2z) x (3x)

= 20y^{2}+30yx+4zy+6zx

= (10y) x (2y) + (10y) x (3x) + (2z) x (2y) + (2z) x (3x)

= 20y

8

Find the product

(4y-x) ( 6x-y )

= 24yx-4y^{2}-6x^{2}+1xy

(4y-x) ( 6x-y )

= 24yx-4y

Solution

= (4y-x) x (6x-y)

= (4y) x (6x) - (4y) x (y) - (x) x (6x) - (x) x (y)

= 24yx-4y^{2}-6x^{2}+1xy

= (4y) x (6x) - (4y) x (y) - (x) x (6x) - (x) x (y)

= 24yx-4y

9

Find the product

(9a+b) ( 6a-6b )

= 54a^{2}-48ab-6b^{2}

(9a+b) ( 6a-6b )

= 54a

Solution

= (9a+b) x (6a-6b)

= (9a) x (6a) - (9a) x (6b) + (b) x (6a) - (b) x (6b)

= 54a^{2}-54ab+6ba-6b^{2}

= 54a^{2}-48ab-6b^{2}

= (9a) x (6a) - (9a) x (6b) + (b) x (6a) - (b) x (6b)

= 54a

= 54a

10

Find the product

(2x-2y) ( 5x-3y )

= 10x^{2}-16xy-6y^{2}

(2x-2y) ( 5x-3y )

= 10x

Solution

= (2x-2y) x (5x-3y)

= (2x) x (5x) - (2x) x (3y) - (2y) x (5x) - (2y) x (3y)

= 10x^{2}-6xy-10yx+6y^{2}

= 10x^{2}-16xy-6y^{2}

= (2x) x (5x) - (2x) x (3y) - (2y) x (5x) - (2y) x (3y)

= 10x

= 10x

11

Find the product

(2x+3y) ( 5y-2z )

= 10xy-4xz+15y^{2}-6yz

(2x+3y) ( 5y-2z )

= 10xy-4xz+15y

Solution

= (2x+3y) x (5y-2z)

= (2x) x (5y) - (2x) x (2z) + (3y) x (5y) - (3y) x (2z)

= 10xy-4xz+15y^{2}-6yz

= (2x) x (5y) - (2x) x (2z) + (3y) x (5y) - (3y) x (2z)

= 10xy-4xz+15y

12

Find the product

(12y+4z) ( 2y+3z )

= 24y^{2}+44yz+12z^{2}

(12y+4z) ( 2y+3z )

= 24y

Solution

= (12y+4z) x (2y+3z)

= (12y) x (2y) + (12y) x (3z) + (4z) x (2y) + (4z) x (3z)

= 24y^{2}+36yz+8zy+12z^{2}

= 24y^{2}+44yz+12z^{2}

= (12y) x (2y) + (12y) x (3z) + (4z) x (2y) + (4z) x (3z)

= 24y

= 24y

13

Find the product

(2x+4y) ( 9y-2z )

= 18xy-4xz+36y^{2}-8yz

(2x+4y) ( 9y-2z )

= 18xy-4xz+36y

Solution

= (2x+4y) x (9y-2z)

= (2x) x (9y) - (2x) x (2z) + (4y) x (9y) - (4y) x (2z)

= 18xy-4xz+36y^{2}-8yz

= (2x) x (9y) - (2x) x (2z) + (4y) x (9y) - (4y) x (2z)

= 18xy-4xz+36y

14

Find the product

(9a+2b) ( 6a+6b )

= 54a^{2}+66ab+12b^{2}

(9a+2b) ( 6a+6b )

= 54a

Solution

= (9a+2b) x (6a+6b)

= (9a) x (6a) + (9a) x (6b) + (2b) x (6a) + (2b) x (6b)

= 54a^{2}+54ab+12ba+12b^{2}

= 54a^{2}+66ab+12b^{2}

= (9a) x (6a) + (9a) x (6b) + (2b) x (6a) + (2b) x (6b)

= 54a

= 54a

15

Find the product

(3a+4b) ( 2a+4b )

= 6a^{2}+20ab+16b^{2}

(3a+4b) ( 2a+4b )

= 6a

Solution

= (3a+4b) x (2a+4b)

= (3a) x (2a) + (3a) x (4b) + (4b) x (2a) + (4b) x (4b)

= 6a^{2}+12ab+8ba+16b^{2}

= 6a^{2}+20ab+16b^{2}

= (3a) x (2a) + (3a) x (4b) + (4b) x (2a) + (4b) x (4b)

= 6a

= 6a

16

Find the product

(3x+3y) ( 4x+5y )

= 12x^{2}+27xy+15y^{2}

(3x+3y) ( 4x+5y )

= 12x

Solution

= (3x+3y) x (4x+5y)

= (3x) x (4x) + (3x) x (5y) + (3y) x (4x) + (3y) x (5y)

= 12x^{2}+15xy+12yx+15y^{2}

= 12x^{2}+27xy+15y^{2}

= (3x) x (4x) + (3x) x (5y) + (3y) x (4x) + (3y) x (5y)

= 12x

= 12x

17

Find the product

(3x+5y) ( x-y )

= 3x^{2}+2xy-5y^{2}

(3x+5y) ( x-y )

= 3x

Solution

= (3x+5y) x (x-y)

= (3x) x (x) - (3x) x (y) + (5y) x (x) - (5y) x (y)

= 3x^{2}-3xy+5yx-5y^{2}

= 3x^{2}+2xy-5y^{2}

= (3x) x (x) - (3x) x (y) + (5y) x (x) - (5y) x (y)

= 3x

= 3x

18

Find the product

(x-4y) ( 2x+3y )

= 2x^{2}-5xy-12y^{2}

(x-4y) ( 2x+3y )

= 2x

Solution

= (x-4y) x (2x+3y)

= (x) x (2x) + (x) x (3y) - (4y) x (2x) - (4y) x (3y)

= 2x^{2}+3xy-8yx-12y^{2}

= 2x^{2}-5xy-12y^{2}

= (x) x (2x) + (x) x (3y) - (4y) x (2x) - (4y) x (3y)

= 2x

= 2x

19

Find the product

(7x-y) ( 9x-2y )

= 63x^{2}-23xy-2y^{2}

(7x-y) ( 9x-2y )

= 63x

Solution

= (7x-y) x (9x-2y)

= (7x) x (9x) - (7x) x (2y) - (y) x (9x) - (y) x (2y)

= 63x^{2}-14xy-9yx+2y^{2}

= 63x^{2}-23xy-2y^{2}

= (7x) x (9x) - (7x) x (2y) - (y) x (9x) - (y) x (2y)

= 63x

= 63x

20

Find the product

(15m-3n) ( 14m-16n )

= 210m^{2}-282mn-48n^{2}

(15m-3n) ( 14m-16n )

= 210m

Solution

= (15m-3n) x (14m-16n)

= (15m) x (14m) - (15m) x (16n) - (3n) x (14m) - (3n) x (16n)

= 210m^{2}-240mn-42nm+48n^{2}

= 210m^{2}-282mn-48n^{2}

= (15m) x (14m) - (15m) x (16n) - (3n) x (14m) - (3n) x (16n)

= 210m

= 210m

Online Test

Start my Challenge

Find the product (9n+8s) (8n+4s)

Find the product (5b+5c) (5b+6c)

Find the product (5a+7b) (a+8b)

Find the product (5q+7r) (7q+6r)

Find the product (4p+10q) (p+8q)

Find the product (10a-c) (9a+c)

Find the product (6b-9c) (9b-5c)

Find the product (3x-4y) (x-8y)

Find the product (6m+s) (5m-s)

Find the product (10x-z) (7x+z)

MATH LEARNING RESOURCES AND TOOLS FOR PERSONALIZED LEARNING